Performance evaluation of multistage adsorber design for mercury removal from produced water - Suboh, Siti Fatimah (2015)
Management of mercury is really important as it is harmful to the environment and human, even though it exists in low concentration. In order to reduce the mercury emitting to environment, the mercury removal process needs to be developed. Adsorption is the well-known process for mercury removal due to the fact that it has low operating cost, simplicity, high efficiency, potential of adsorbent regeneration, and sludge free process. The mercury removal in the multistage adsorber is preferable compared to single stage adsorber as the total cross-sectional area increases with increasing number of adsorber stages and thus increasing the mercury removal efficiency. In this study, the design of multistage adsorber to remove CH3Hg(II) and Hg(II) from inlet solution by using the CP adsorbents was investigated so that the optimum amount of CP adsorbent, the number of stages and the optimum contact time for selected mercury removal efficiency can be determined. Optimization of the CP-Pure amount was calculated for selected removal efficiency (i.e. 50, 60, 70, 80, and 90 %) of CH3Hg(II) and Hg(II) ions for initial concentration of 0.6 g/m3 treated in various inlet solution volumes. As the inlet solution volume increased, the adsorbent amount increased. The adsorbent amount also increased with increasing the removal efficiency. The treated CP adsorbents were efficient than CP-Pure adsorbent as the adsorption process only needed less amount of treated CP adsorbents to remove CH3Hg(II) and Hg(II) at the same conditions. The optimum stage number for 99% removal of CH3Hg(II) using CP-Pure adsorbent and inlet solution volume of 2.5m3 was four, while the total amount of the CP-Pure adsorbent was 1.64 kg (0.41 kg for each stage). For the same conditions, the same stage number was also obtained for Hg(II) with the CP-Pure adsorbent amount of 0.13 kg (0.09 kg for each stage). For 99% removal of CH3Hg(II) and Hg(II) from 0.6 g/m3 initial concentration and inlet solution volume of 2.5 m3, the optimum time was 2.17 and 1.25 min, respectively with four stages.